Surveillance strategies for antimicrobial resistance (AMR) bacteria in poultry and dairy implemented in two provinces in Kenya with potential for nation-wide adoption and use - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
Antimicrobial resistance (AMR) surveillance and monitoring detects and tracks changes and trends in microbial populations in livestock production systems including drug-resistant microorganisms.